THE EFFECT OF APPLYING SYNECTICS MODEL ON STUDENTS ACHIEVEMENT IN SPEAKING - Larasati, Larasati; Asrul, Nurmahyuni; Amaniarsih, Dwi Suci (Pedagogi: Jurnal Ilmiah Pendidikan, 2024)
This research uses an experimental design with the main objective of finding out how much influence the application of the Synectics model has on students' speaking ability when they are given the help of picture media. The study was conducted at SMK Telkom 2 Medan, which is located at Jalan Halat No. 68, Kota Matsum II, Kec. Medan Area, Medan City. The population of this study was all eleventh grade students (hospitality XI-1 andhospitality XI-2), consisting of 22 students. The sample was divided into two classes: the control group, which received instruction through lectures, and the experimental group, which was taught using the synectic model. The result showed that from the analysis of teaching and learning speaking, itcan be concluded that there was an effect of applying the synectics model on the students' speaking skills by using picture media, as evidenced by thet calculation > table (3,323 > 1,682). And it was discovered that the entire percentage of the effect of employing the synectics model on the students' speaking competence by using picture media was 41%, with the remaining 59% influenced by other factors.